A case of sulfhemoglobinemia in a child with chronic constipation. (2017) - George, Ashish; Goetz, Danielle
Abstract: Sulfhemoglobinemia is a rare condition in which a sulfur atom oxidizes the heme moiety in hemoglobin, making the hemoglobin incapable of carrying oxygen and leading to hypoxia and cyanosis. This condition has been described in patients taking sulfur medications or who have cultured hydrogen sulfide producing intestinal bacteria such as Morganella morganii . This case describes a pediatric patient who was found to have cyanosis on two occasions of urinary tract infection in the setting of chronic constipation, with confirmed sulfhemoglobinemia during the second admission. Sulfhemoglobinemia due to increases in sulfur producing intestinal bacteria led to cyanosis and low oxygen saturations. The patient had an incidental finding of a pulmonary arteriovenous malformation (AVM) but had a normal PAO2 so was not hypoxemic though she was cyanotic. Low oxygen saturations by pulse oximetry may be explained by dyshemoglobinemia as opposed to true arterial hypoxemia; the importance of measuring an arterial blood gas in cases of cyanosis is paramount.